2023
DOI: 10.1186/s12936-023-04648-6
|View full text |Cite
|
Sign up to set email alerts
|

Can the performance of pyrethroid-chlorfenapyr nets be reduced when combined with pyrethroid-piperonyl butoxide (PBO) nets?

Abstract: Background Pyrethroid-chlorfenapyr (CFP) and pyrethroid-piperonyl butoxide (PBO) nets are being scaled across endemic countries to improve control of malaria transmitted by pyrethroid-resistant mosquitoes. CFP is a pro-insecticide requiring activation by mosquito cytochrome P450 monooxygenase enzymes (P450s) while PBO improves pyrethroid potency by inhibiting the action of these enzymes in pyrethroid-resistant mosquitoes. The inhibitory action of PBO against P450s may thus reduce the efficacy o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This antagonistic effect of PBO on the efficacy of chlorfenapyr has been documented in insect pests (31,45). Chlorfenapyr is a proinsecticide whose transformation into a toxic metabolite (tralopyril) is catalysed by cytochrome P 450 enzymes (CYPs), hence the reduction in activity when CYPs are inhibited by PBO (12,13,47,48). This finding suggests that downregulation of some CYPs may be a potential mechanism Anopheles could exploit to develop resistance to chlorfenapyr as is the case in the two-spotted spider mite, Tetranychus urticae (49).…”
Section: Discussionmentioning
confidence: 99%
“…This antagonistic effect of PBO on the efficacy of chlorfenapyr has been documented in insect pests (31,45). Chlorfenapyr is a proinsecticide whose transformation into a toxic metabolite (tralopyril) is catalysed by cytochrome P 450 enzymes (CYPs), hence the reduction in activity when CYPs are inhibited by PBO (12,13,47,48). This finding suggests that downregulation of some CYPs may be a potential mechanism Anopheles could exploit to develop resistance to chlorfenapyr as is the case in the two-spotted spider mite, Tetranychus urticae (49).…”
Section: Discussionmentioning
confidence: 99%
“…gambiae s.l., and An. funestus (Corbel et al, 2010;Ketoh et al, 2018;Oumbouke et al, 2019;Barreaux et al, 2022;Menze et al, 2022;Ngufor et al, 2022;Syme et al, 2023a;Zahouli et al, 2023). Only one study showed an increase in blood-feeding rate after PBO net exposure in Cameroon (Corbel et al, 2010), whilst no difference was seen between PBO and pITNs in Benin, Cote d'Ivoire, and Cameroon (Koudou et al, 2011;Pennetier et al, 2013;Menze et al, 2020).…”
Section: Reduction In Blood Feedingmentioning
confidence: 99%
“…gambiae s.l. from Burkina Faso, Benin, Cameroon, and Cote d'Ivoire (Bayili et al, 2017;Camara et al, 2018;Syme et al, 2023a;Tchouakui et al, 2023). One study on RG in Cameroon shows a reduced BF rate (Tchouakui et al, 2023).…”
Section: Reduction In Blood Feedingmentioning
confidence: 99%
See 2 more Smart Citations